Evaluation of self-healing properties of asphalt mixture containing steel slag under microwave heating: Mechanical, thermal transfer and voids microstructural characteristics - Liu, Jianan; Zhang, Tonghuan; Guo, Haoyan; Wang, Zhenjun; Wang, Xiaofeng (Journal of cleaner production, 2022)
In this work, the asphalt mixture was prepared by partially replacing limestone with steel slag, and the self-healing properties under microwave heating (MH) were studied. Firstly, the element compositions of steel slag and its absorbing heating mechanism were analyzed. Then, five groups of semicircular bending (SCB) samples with different steel slag content were prepared, and the self-healing performance of the steel slag asphalt mixture was evaluated by the crack-healing test. Subsequently, the surface temperature and thermal transfer process of MH 40 s in SCB and crack propagation zone (CPZ) were compared and analyzed. Finally, the Marshall sample before and after MH were scanned by X-ray computed tomography (CT). The results show that steel slag has good wave absorption performance because it contains a lot of metal oxides. The initial strength of steel slag asphalt mixture does not decrease significantly, but its self-healing index fracture energy healing rate (FEHR) is obviously higher than that of the conventional mixture. And the self-healing properties of samples with higher steel slag content will be better. Besides, compared with the total average temperature of SCB, the FEHR of the sample is more correlated with the surface temperature of CPZ after MH. Based on CT scanning, steel slag is uniformly distributed in the mixture. An appropriate MH cycle can effectively improve the voids microstructural of the mixture, but an excessive MH cycle can bring negative effects.